ANALISIS INTERNAL CONTROL, KOMPETENSI SUMBER DAYA MANUSIA DAN PENERAPAN E-COMMERCE TERHADAP SISTEM INFORMASI AKUNTANSI PADA BANK SYARIAH YANG TERDAFTAR DI BANK INDONESIA - Rujito Rujito; Anna Cholifah; Diah Iskandar (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2016)
This study aimed to test the internal controls, human resources competencies and application of e-commerce to the accounting information system. The object of this study is that Islamic banks registered in Bank Indonesia. Data of research was received by data collection techniques literature and field studies in the form of questionnaires. The sampling technique used purposive sampling. The population in this study are employees of Islamic banks listed on Bank Indonesia. The sample are Islamic banks have more than one branch and sub-branch offices in Jakarta. The results showed that the internal control variables, the competence of human resources and implementation of e-commerce affect the accounting information system.